Loss of MYSM1 inhibits the oncogenic activity of cMYC in B cell lymphoma. Issue 14 (11th June 2021) - Lin, Yun Hsiao; Wang, HanChen; Fiore, Amanda; Förster, Michael; Tung, Lin Tze; Belle, Jad I; Robert, Francis; Pelletier, Jerry; Langlais, David; Nijnik, Anastasia
Abstract: MYSM1 is a chromatin‐binding protein, widely investigated for its functions in haematopoiesis in human and mouse; however, its role in haematologic malignancies remains unexplored. Here, we investigate the cross‐talk between MYSM1 and oncogenic cMYC in the transcriptional regulation of genes encoding ribosomal proteins, and the implications of these mechanisms for cMYC‐driven carcinogenesis. We demonstrate that in cMYC‐driven B cell lymphoma in mouse models, MYSM1‐loss represses ribosomal protein gene expression and protein synthesis. Importantly, the loss of MYSM1 also strongly inhibits cMYC oncogenic activity and protects against B cell lymphoma onset and progression in the mouse models. This advances the understanding of the molecular and transcriptional mechanisms of lymphomagenesis, and suggests MYSM1 as a possible drug target for cMYC‐driven malignancies.